PRODUCTION AND REPRODUCTION PERFORMANCE OF NELLORE SHEEP IN (NATIVE BREEDING) CHITTOOR DISTRICT OF ANDHRA PRADESH - B. PUNYA KUMARI, M. RANI, B. EKAMBARAM and (The Journal of Research, PJTSAU, 2019)
The analysis of field data on 1350 Nellore Jodipi sheep maintained by farmers under field conditions of Andhra Pradesh revealed that the effect of division and sex had significant (P<0.01) influence on body weights at majority of ages studied. The overall least square means for body weight at 2, 4, 6 and 8-teeth age were 35.26 ±0.23, 38.45 ±0.13, 39.53 ± 0.32 and 40.06 ± 0.33 kg, respectively. Males were heavier than females in all age groups and the differences of body weights were 10.67, 10.44, 8.84 and 7.37kg, respectively at 2, 4, 6 and 8-teeth ages. The overall least squares means for age at first service, age at first lambing, lambing interval and gestation period were 689.09 ± 1.23 days, 841.04 ± 1.21 days, 383.43 ± 0.48 days and 151.95 ± 0.08 days, respectively.